Effect of Si Content on Microstructure and Magnetic Properties of Electrical Steel - Bui, Anh-Hoa; Nguyen, Minh-Hoang (Journal of Sustainable Materials Processing and Management, 2026)
Electrical steel (or silicon steel) is popularly used to manufacture motors and transformers. This paper presents the change in microstructure and magnetic properties of several electrical steels containing different amounts of silicon (Si). The samples were cut from different steel sheets, each 0.7 mm thick, for optical observation and magnetic testing. The investigation showed that the homogeneous microstructure of the steels consisted of ferrite with different grain sizes varying from 17 to 35 µm. The grain size increased with increasing Si content, in turn improving the magnetic properties of the studied electrical steel. Among the studied steels, the sample M4 containing 1.47 wt.% Si showed the best magnetic properties, including a coercivity (Hc) of 2.425 Oe, residual magnetism (Mr) of 0.0114 emu, saturation magnetization (Ms) of 7.11 emu and maximum energy product (BHmax) of 26947 MGOe. The obtained results will be useful and suggest to Vietnamese steelmakers to produce high-efficiency electric steel with proper chemical compositions.